Negative element balance according to a survey for consumption of some essential elements in cases of patients with inflammatory bowel diseases - Szentmihályi, Klára (Acta Biologica Szegediensis, 2009)
Malnutrition is a characteristic feature of inflammatory bowel diseases (IBD), often due to unhealthy nutritional habits. Therefore, nutritional habits (intake of vegetables and fruits) and element content in erythrocytes have been investigated. 50 IBD patients (25 male, 25 female) and 50 healthy volunteers (35 male, 15 female) were asked to complete a questionnaire. In addition to routine laboratory parameters, Ca, Cu, Fe, Mg, Mn, P, S and Zn content in erythrocytes were determined with ICP-OES. Decreased level of Ca (0.975 ± 0.440 μg/g), Mg (1.02 ± 0.24 μg/g) and Zn (0.776 ± 0.482 μg/g) was observed in IBD patients at P<0.05 level compared to the control (2.90 ± 2.25 μg/g, 18.28 ± 9.66 μg/g and 1.05 ± 0.48 μg/g). IBD patients consume similar foodstuffs to healthy people although in lesser amount. The intake of nutritional antioxidants was almost the same in both groups, whereas element intake differed because of diverse nutritional habits. According to the survey, in Hungary healthy people consume about 18-66% of essential element requirements. In the case of IBD patients the situation is worse (15-60%) because of lesser intake and malabsorption. Lowest element intakes were observed for Ca and Zn. The mineral element imbalance in IBD patients probably contributes to their deficiency. Since IBD patients and the controls are on similar diet, latent element deficiency may develop in healthy volunteers which may enhance the risk of metabolic diseases.